Kepasrahan Diri Sebagai Perventif Radikalisme Dalam Mewujudkan Harmonisasi Lintas Budaya - Agus Sholahudin Shidiq; Farida Isroani (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2022)
This research aims to examine Self-Submission as a Preventive of Radicalism in Realizing Cross-Cultural Harmonization. Tawakal is a work of the heart, spiritual work, a worship whose meaning is very difficult, but needs to be implemented in reality. Tawakal must be linked to the law of cause and effect, so that tawakal is no longer defined as being silent without any activity. Tawakal will encourage a person to have a sense of optimism and courage in facing all life's problems. All of these values ​​exist in the religions of Islam, Christianity (Protestant and Catholic), Hinduism and Buddhism. The equal value of surrendering oneself to God is manifested in worship activities both individually and in congregation. In all religions there is a value of servitude which includes the value of surrender.